Analysis of the database use by the students of industrial engineering in hybrid mode post Covid-19 - Mamani-Calcina, Jorge (2023)
The COVID 19 pandemic forced many universities to move on from an in-person mode to a remote work and on-line classes in order to continue the academic activities. One of the measures to stop the transmission of the virus was the discontinuation of the in-person activities. It was a challenge for many to meet this radical change in such a short time; a challenge that had to be accepted worldwide considering information and communication technologies as a critical factor. At this time, the COVID 19 is under control with a significant decrease in the number of cases, this situation has allowed many universities to returned to the in-person activities and other universities have chosen a hybrid mode that still allows the on-line activities. Therefore, this work studies the hybrid mode adopted by the university where the Industrial Engineering school belongs. One of the most relevant information resources in these days has been the database which is available in libraries. This study analyzes the use of databases during the pandemic until the present by the students of the Industrial Engineering school in a hybrid mode. It has been possible to obtain the statistics of access to the database with positive results toward its use by the students. The students affirm that they are satisfied with the infrastructure, and the physical and electronic resources in the hybrid modality. The results also indicate an increase in the access to the databases. As a conclusion, there was an increase in the annual enquiries/visits from the students of the Industrial Engineering school, also, not all the databases the students got access were related with the Industrial Engineering school. This indicates that the students have adapted to the hybrid modality taking advantage of the databases provided by the university.